2020
DOI: 10.1182/blood.2019002887
|View full text |Cite
|
Sign up to set email alerts
|

External validation of models for KIR2DS1/KIR3DL1-informed selection of hematopoietic cell donors fails

Abstract: Several studies suggest that harnessing natural killer (NK) cell reactivity mediated through killer cell immunoglobulin-like receptors (KIRs) could reduce the risk of relapse after allogeneic hematopoietic cell transplantation. Based on one promising model, information on KIR2DS1 and KIR3DL1 and their cognate ligands can be used to classify donors as KIR-advantageous or KIR-disadvantageous. This study was aimed at externally validating this model in unrelated donor hematopoietic cell transplantation. The impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 40 publications
(58 reference statements)
1
35
0
Order By: Relevance
“…Against this background we set out to validate an HLA-matched unrelated donor selection algorithm for patients with AML and MDS which was essentially aimed at reducing the inhibitory potential of donor NK cells and increasing the activating potential by donor selection based on information on KIR2DS1 and KIR3DL1 ( 12 , 13 ). We recently reported results of a study in AML patients where we failed to replicate the findings of the original report ( 23 ). Here, we present the data on patients with MDS or secondary AML.…”
Section: Introductionmentioning
confidence: 76%
“…Against this background we set out to validate an HLA-matched unrelated donor selection algorithm for patients with AML and MDS which was essentially aimed at reducing the inhibitory potential of donor NK cells and increasing the activating potential by donor selection based on information on KIR2DS1 and KIR3DL1 ( 12 , 13 ). We recently reported results of a study in AML patients where we failed to replicate the findings of the original report ( 23 ). Here, we present the data on patients with MDS or secondary AML.…”
Section: Introductionmentioning
confidence: 76%
“…Since NK cells are the first lymphocytes to reconstitute in patients after HSCT (26), efforts have been made to exploit their potential to elicit a rapid and targeted immune response against remaining leukemic cells (27)(28)(29)(30)(31)(32). Recent research indicates an impact of donor KIR genotype on the outcome of HSCT, but results remain controversial (33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…These findings have been adopted in practice, as when otherwise similarly HLA-matched allogeneic or haploidentical HSCT donors are available, HSCT donor selection algorithms consider KIR profiles as a donor selection criteria ( 35 , 37 39 ). However, selection of KIR ligand mismatches in HSCT remains an active area of investigation, as a recent study found that optimization of donors based on KIR2DS1 and KIR3DL1 expression did not provide a survival benefit ( 40 ).…”
Section: Introductionmentioning
confidence: 99%